Implementation Of Informatics In Improving The Quality Of Learning - Betsi Rooroh; Toban Tiku Pairunan; Marchya Kaseke; Ni Made Devia Anjani; Fauzy Ahmad Inaku; Alfiando Makapedua (Jurnal Syntax Admiration, 2024)
The integration of informatics in education has been pivotal in improving the quality of learning by providing personalized, flexible, and efficient learning experiences. This research aims to explore the impact of informatics tools, such as digital platforms, adaptive learning technologies, and data analytics, on teaching and learning outcomes. Utilizing a mixed-method approach, the study involved a needs assessment, tool development, pilot testing, and continuous evaluation. Data was collected through surveys, interviews, and performance metrics to analyze the effectiveness of informatics in educational settings. The findings reveal that informatics facilitates personalized learning paths, enabling students to progress at their own pace, which enhances engagement and retention. Adaptive technologies provide real-time feedback and tailored content, addressing individual learning needs effectively. Moreover, data-driven insights empower educators to make informed decisions and intervene proactively to support students. The implementation of these tools has also streamlined administrative tasks, allowing educators to focus more on instructional quality. This study concludes that informatics significantly improves learning outcomes, operational efficiency, and inclusivity in education. However, challenges such as ensuring equitable access to technology, providing adequate training for educators, and addressing data privacy concerns must be tackled to optimize the benefits. The implications of this research emphasize the need for continued investment in technological infrastructure and professional development to sustain advancements in educational quality